Genetic diversity and population structure of the indigenous goat population in Tunisia's northwest - I. BenSouf; I. Dhib; S. Bejaoui; H. Ouled Ahmed; H. Khemiri; N. M'Hamdi (Archives Animal Breeding)
Elucidating genetic diversity is critical for improving breeding strategies. To this end, the present study investigated the genetic diversity and population structure of the local goat population sampled from the northwestern region of Tunisia. The genetic variability was estimated using seven microsatellites, which revealed high diversity and genetic population clustering with a dispersed geographical distribution. All of the markers showed a significant genetic polymorphism, with an average of 18 alleles. Thus, 123 alleles were detected in the seven loci of the six studied populations. This result reflects the existence of a significant polymorphism within the local goat population. Overall, the highest HO was 0.952, and the highest HE was 0.942. Furthermore, the goat population demonstrated negative FIS (−0.177). This negative value shows an overall excess of heterozygotes, suggesting the absence of inbreeding. Analysis of molecular variance (AMOVA) revealed that genetic differences within the population explained 92.4 % of the variation. A low average FST (0.076) suggests intermixing among Tunisian goats. Genetic distance values range from 0.319 to 0.985.